Sodium-doped hydroxyapatite nanopowder through sol-gel method: synthesis and characterization - Pusparini, Erlani; Sopyan, Iis; Abd Shukor , Mohamad Hamdi; Ramesh, Singh (Trans Tech Publications, 2011)
The nanocrystalline HA powders were produced through sol-gel method which employed calcium nitrate tetrahydrate [Ca(NO3)2.4H2O] and diammonium hydrogen phosphate [(NH4)2HPO4] as calcium and phosphorous precursors. Sodium ion (Na+) is one of the trace elements found in biological apatite and believed to have important effect in its performance. The concentrations of sodium dopant were varied from 0 mol% until 15 mol% by using sodium nitrate (NaNO3) as the source of dopant. Characterization of nanopowders was investigated by using X-ray diffraction (XRD), Fourier transform infra red (FTIR) and Transmission Electron Microscope (TEM). XRD analysis revealed that there are no other phases exist in the synthesized powder, evinced single phase of HA and a trend shows an increase of cristallinity with increase of sodium dopant concentration. While the TEM images showed evidence that the particle sizes were bigger with the increasing sodium concentration, showing the effect of sodium dopant on the densification of the powder.